2020
DOI: 10.1007/s40744-020-00220-9
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Online Qualitative Study to Explore the Symptom Experience of Patients with Primary Sjögren’s Syndrome

Abstract: Introduction: Primary Sjögren's syndrome (pSS) is a complex, heterogenous autoimmune disease; no immunomodulatory drug has demonstrated efficacy, and no current treatments target the underlying cause. This study aimed to explore the disease and treatment experiences of patients with pSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Another study found fatigue and pain to be the main predictors of poor QoL in patients with pSS regardless of disease activity, age, schooling, marital status, work disability and fibromyalgia (11). Though such complications are not life-threatening, the chronicity can lead to heavy debility and reduced quality of life, affecting not only daily activities and social life, but also career and finances (12).…”
Section: Introductionmentioning
confidence: 99%
“…Another study found fatigue and pain to be the main predictors of poor QoL in patients with pSS regardless of disease activity, age, schooling, marital status, work disability and fibromyalgia (11). Though such complications are not life-threatening, the chronicity can lead to heavy debility and reduced quality of life, affecting not only daily activities and social life, but also career and finances (12).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the online format may prevent participants from in-depth investment in their responses, potentially prompting more shallow-level answers than we were hoping for. Recent studies have reported sufficient quality for qualitative data collected online [ 79 , 80 ], and there is an increasing number of qualitative studies using online platforms [ 81 85 ]. In addition, participants responses in the current study all seemed sensible to the coder.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the low pre-index prevalence of malaise/fatigue and/or pain in patients with pSS. Despite being reported as the most bothersome symptom of pSS [ 20 , 21 ], only 1.2% of patients with pSS had a recorded diagnosis for malaise/fatigue in the pre-index period. However, the diagnosis code for malaise/fatigue had limited utility since further clinical data and laboratory data are not captured in the Swedish national patient register.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to dryness, patients with pSS experience significantly more severe pain and fatigue than the general population, resulting in reduced physical functioning, emotional well-being, social functioning, and cognitive impairment [ 18 ]. Fatigue is cited by patients as the most severe symptom and the one they most wish they could change [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%